Android-Based Doctor E-Consultation Application Using Scrum - Andika, Rendy; Zufria, Ilka; Triase, Triase (Sinkron : jurnal dan penelitian teknik informatika, 2023)
The standard service hospitals provide for their patients is a doctor's consultation. However, many patients need help accessing this service due to having to go to the hospital, queuing, and long waiting times. So that patients no longer have difficulty accessing consulting services, we need a system that can speed up consulting activities. The system development method used in Android-based e-consulting applications is the Scrum method. The system development process is somewhat accelerated using the Scrum methodology because all development activities require planning and timing for each sprint, starting with sprint planning, continuing through the daily scrum, sprint review, and sprint retrospective, which is repeated at each sprint to avoid delays in application development. By offering consultation services online, this system allows patients to access existing facilities and more efficiently supports the improvement of consulting services at existing hospitals, especially in Indonesia.